Stiffness, Workspace Analysis and Optimization for 3UPU Parallel Robot Mechanism - Cui Guohua; Wei Bin; Wang Nan; Zhang Yanwei (Institute of Advanced Engineering and Science, 2013)
In this paper, an approach based on the particle swarm optimization is used to optimize the workspace and global stiffness of the 3UPU mechanism simultaneously due to the fact that the workspace is affected while optimizing the stiffness of the mechanism and vice versa. When optimizing one particular performance, one needs to have an objective function. Here the workspace volume of the mechanism is used as an objective function to evaluate the workspace performance of the mechanism. The leading diagonal elements of the stiffness matrix represent pure stiffness in each direction, but this stiffness changes when the moving platform position changes. We call this stiffness as local stiffness. When using the local stiffness as an objective function for stiffness optimization, it can only represent the stiffness in one particular position. Here the global stiffness of the mechanism is used as an objective function to optimize the stiffness of the mechanism. The global stiffness represents mean stiffness over the workspace. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3276